Youth and Politics: Political Education and Participation among Youth (Aydin Gürlevik, Klaus Hurrelmann and Christian Palentien (eds.): Jugend und Politik: Politische Bildung und Beteiligung von Jugendlichen) - Christof Wittmaack (Intergenerational Justice Review)
No abstract